Bandgaps, Dynamics and Stability of Multi-Span Beam Rested on Periodically Arranged Exterior Supports - Ghazaryan, K. B. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
In the framework of the Floquet theory formation of flexural frequency bandgaps is considered for a beam in tension rested on periodically arranged rigid or elastically constraint intermediate exterior supports. In the case of an axial compressive force action the elastic stability of such beams is also discussed. Ֆլոկեի տեսության շրջանակում դիտարկված են ձգված հեծանի ծռման հաճախությունների արգելված գոտիների ձևավորման խնդիրներ: Հեծանը դրված է պարբերաբար դասավորված կոշտ կամ առաձգական միջանկյալ արտաքին հենարաններին: Քննարկվում է նաև այդպիսի հեծանների կայունությունն առանցքային սեղմող ուժի ազդեցության դեպքում: В рамках теории Флоке рассмотрены задачи формирования запрещенных зон изгибных частот растянутой балки, покоящейся на периодически расположенных жестких или упругих промежуточных внешних опорах. Обсуждается также устойчивость таких балок в случае действия осевой сжимающей силы.
Keywords: Mechanics